An atypical presentation of talon cusp: Double talon cusps (Indian Journal of Case Reports, 2024)
Talon cusp is an uncommon developmental anomaly resulting in an extra cusp or cuspal projection on an anterior tooth consisting of normal enamel, dentin, and varying degrees of pulp tissue. Talon cusp shows varied presentations of which the palatal talon cusp has been the most common of all. The management requires an extensive understanding of this clinical entity and the complications associated with its occurrence. In this case series, we are reporting double talon cusps which is a rarity itself, involving the palatal aspect of maxillary central incisors.